Mapping the diagnosis of autism spectrum disorders in children aged under 7 years in Australia, 2010–2012. Issue 6 (6th April 2015) - Bent, Catherine A; Dissanayake, Cheryl; Barbaro, Josephine
Abstract: Objectives: To investigate the frequency and age at diagnosis of autism spectrum disorder (ASD) in children aged under 7 years living in Australia. Design and participants: Analysis of de‐identified data on 15 074 children aged under 7 years registered with the Helping Children with Autism Package (HCWAP; a program that provides funding for access to early intervention and support services throughout Australia) between 1 July 2010 and 30 June 2012. Main outcome measures: Age at diagnosis of ASD as confirmed by a paediatrician, psychiatrist and/or multidisciplinary team assessment. Results: The average age at diagnosis of ASD in children registered with the HCWAP is currently 49 months, with the most frequently reported age being 71 months. Differences were evident in age at diagnosis across states, with children in Western Australia and New South Wales being diagnosed at a younger age. Across Australia, 0.74% of the population of children aged under 7 years are currently diagnosed with ASD and registered with the HCWAP. A higher proportion of children were registered with the HCWAP in Victoria compared with other states. There was no difference in age at diagnosis between Indigenous and non‐Indigenous Australians, but children from a culturally and linguistically diverse background were diagnosed 5 months earlier than other children. Conclusions: There may be a substantial gap between the age at which a reliable and accurate diagnosis of ASD is possible and the average age that children are currently diagnosed. The frequency of ASD diagnoses in Australia has increased substantially from previously published estimates.